Gifted Females’ Attitudes and Perceptions of Learning Environment in Technology-Based Science Classrooms in Singapore - Sundari, G. (Curtin University, 2016)
The effectiveness of using technology in science classrooms in Singapore was evaluated using learning environment and attitude scales. For a sample of 722 secondary-school students, the scales for which differences between technology-based and regular classes were statistically significant (Investigation, Task Orientation, Collaboration, Computer Usage, Formative Assessment, Attitudes towards Computers and Self-regulation), the effect sizes were 0.36, 0.40, 0.22, 1.09, 0.27, 0.37 and 0.31 standard deviations, respectively.